Bahasa Binte - Syamsumarlin .; Muh. Sarjono (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2014)
Based on description above, the formulation of problem in this research is how the use and function of Binte language on teenager in Wamponiki District Katobu Village, Muna Regency. The research aims are to know and describe the use and function of Binte language on teenagers in Wamponiki District Katobu Village, Muna Regency. The results show that Binte language is something which can not be liberated by teenagers in P & K street because Binte language is the unity language of them and also the language become a trend in Raha city. Based on the function of Binte language which is used by teenagers in P & K street (Tagorez Gank), Binte language is something to tell about the happiness, ennoyed, sadness, and etc. It has functions to make contact with another people and as a thing to express togetherness over the user. Keywords: the use and function of language, binte language,slang,muna regency